Perlindungan Hukum Terhadap Anak Dari Eksploitasi Seksual - Ayu Intan Novelianna Setyono; Hadibah Zachra Wadjo; Yonna Beatrix Salamor (Faculty of Law, Universitas Pattimura, 2021)
Introductioan: Legal Protection of Children from Sexual Exploitation is regulated in Law Number 35 of 2014 concerning Amendments to the Protection Law Number 23 of 2002 concerning Child Protection. The number of cases of sexual exploitation of children raises concerns, because it will cause suffering both physically and psychologically so that it affects the growth and development of children.Purposes of the Research: Knowing and analyzing the form of legal protection for children from sexual exploitation and what obstacles are encountered in protecting children from sexual exploitation.Methods of the Research: This study uses a normative juridical method with legal materials used in the study are primary, secondary and tertiary with the use of literature study techniques in the form of international legal regulations, scientific papers and literature.Results of the Research: Based on the results of research on the forms of legal protection for children from sexual exploitation and what obstacles are encountered in protecting children from sexual exploitation, namely the definition of children according to the law, sexual violence and its forms, sexual exploitation in statutory regulations, and child protection in Indonesia, the constraints in protecting children from sexual exploitation and law enforcement on the protection of children from sexual exploitation.